Investigation on Calculation Method of Permeability Coefficient in the Consolidation Process of Cohesive Soil - Mei Zhou; Faning Dang; Jiulong Ding; Le Zhang; Xinyu Liang (Geofluids)
In order to study the permeability characteristics of cohesive soil in the consolidation process more accurately, in this work, the pores occupied by the combined water were defined as invalid pores, and the effective pores and ineffective pores were decoupled to study the relationship between effective pores and permeability coefficient. The widely used empirical formulas of the permeability coefficient were modified, and the empirical formulas of the permeability coefficient suitable for the consolidation process of cohesive soil were obtained. Combined with the e−lgσ relationships of normally consolidated soil, underconsolidated soil, and overconsolidated soil, the formulas of permeability coefficient, which considering the influence of initial consolidation state and consolidation stress, in the consolidation process of cohesive soil, were proposed. Finally, the rationality of the new formulas proposed in this paper was analyzed by indoor consolidation-permeability test and existing research. The results showed that the permeability coefficient of cohesive soil in the consolidation process predicted by the new formulas were more consistent with the measured average value. This study possesses practical engineering significance to solve the problem of foundation consolidation settlement.